Impacto del VIH/sida sobre la calidad de vida: metaanálisis 2002-2012 (2014)
ElVIH/Sidaesunainfeccióncrónicaquetrasciendeeldominiobiológico,afectandoalasrelacionessociales,lasaludmental,losaspectoseconómicosylacalidaddevida.Elobjetivodelestudiofueevaluarlapercepcióndelacalidaddevidarelacionadaconlasalud(CVRS)enpersonasconVIH/sida.